2021
DOI: 10.1038/s41396-021-01149-9
|View full text |Cite
|
Sign up to set email alerts
|

Toward quantifying the adaptive role of bacterial pangenomes during environmental perturbations

Abstract: Metagenomic surveys have revealed that natural microbial communities are predominantly composed of sequence-discrete, species-like populations but the genetic and/or ecological processes that maintain such populations remain speculative, limiting our understanding of population speciation and adaptation to perturbations. To address this knowledge gap, we sequenced 112 Salinibacter ruber isolates and 12 companion metagenomes from four adjacent saltern ponds in Mallorca, Spain that were experimentally manipulate… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
31
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 18 publications
(32 citation statements)
references
References 63 publications
1
31
0
Order By: Relevance
“…Samples CM, DZ, and UM yielded only isolates that each was assigned to a different CV and were not used for the subsampling calculations. Samples and isolates recovered from the Mallorca solar salterns are named according to the different ponds: control (C), dilution (D), and unshaded (U) at three time points: time-zero (Z), 1-week (W), and 1-month (M) (e.g., sample "UM" denotes Unshaded at 1 month) (22). The sample and isolates from Fuerteventura area denoted by "FV" in the name.…”
Section: Methodsmentioning
confidence: 99%
“…Samples CM, DZ, and UM yielded only isolates that each was assigned to a different CV and were not used for the subsampling calculations. Samples and isolates recovered from the Mallorca solar salterns are named according to the different ponds: control (C), dilution (D), and unshaded (U) at three time points: time-zero (Z), 1-week (W), and 1-month (M) (e.g., sample "UM" denotes Unshaded at 1 month) (22). The sample and isolates from Fuerteventura area denoted by "FV" in the name.…”
Section: Methodsmentioning
confidence: 99%
“…The core genes in a pangenome are present in each individual while the remaining genes are considered accessory ( Brockhurst et al 2019 ). Pangenome size and structure vary across bacterial species ( Maistrenko et al 2020 ), and pangenomic diversity is important for bacterial adaptation in environmental species, where accessory genes are often niche-specific ( Kashtan et al 2014 ; Liao et al 2021 ; Conrad et al 2022 ). To understand microbial adaptation, it is thus crucial to understand the evolutionary processes that shape pangenome diversity.…”
Section: Introductionmentioning
confidence: 99%
“…This discovery is also important in medical microbiology; for instance, in identifying which population is the causative agent of disease ( Pena-Gonzalez et al, 2019 ). More recent work has even shown that intermediate identity genotypes, for example, sharing 85–95% ANI, when present, are ecologically differentiated and thus, should probably be considered distinct species ( Conrad et al, 2021 ; Rodriguez-R et al, 2021 ), rather than representing cultivation (or other sampling) biases ( Murray et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%